If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2t + -0.71) = 0.9(1.4 + -1t) Reorder the terms: 3(-0.71 + 2t) = 0.9(1.4 + -1t) (-0.71 * 3 + 2t * 3) = 0.9(1.4 + -1t) (-2.13 + 6t) = 0.9(1.4 + -1t) -2.13 + 6t = (1.4 * 0.9 + -1t * 0.9) -2.13 + 6t = (1.26 + -0.9t) Solving -2.13 + 6t = 1.26 + -0.9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '0.9t' to each side of the equation. -2.13 + 6t + 0.9t = 1.26 + -0.9t + 0.9t Combine like terms: 6t + 0.9t = 6.9t -2.13 + 6.9t = 1.26 + -0.9t + 0.9t Combine like terms: -0.9t + 0.9t = 0.0 -2.13 + 6.9t = 1.26 + 0.0 -2.13 + 6.9t = 1.26 Add '2.13' to each side of the equation. -2.13 + 2.13 + 6.9t = 1.26 + 2.13 Combine like terms: -2.13 + 2.13 = 0.00 0.00 + 6.9t = 1.26 + 2.13 6.9t = 1.26 + 2.13 Combine like terms: 1.26 + 2.13 = 3.39 6.9t = 3.39 Divide each side by '6.9'. t = 0.4913043478 Simplifying t = 0.4913043478
| 2-3/8x=7 | | x+33=98 | | 0.12y+0.06(y+2000)=1020 | | 6x+5=-9x+6 | | -3y-15= | | 26=8-m | | 48=15+.05x | | .16x+.6(x-4)=.01(2x-1) | | 15-w/4=23 | | 112=7xb | | -1/2h=4 | | -3+.66x=3 | | 6y-2-4y+1=0 | | -1/10x+8=46 | | 6m+3m+6=-2m+-7 | | 12/18x+6/9=4x+2 | | 5x+12/3+120=174 | | 7y-10-4y+8=0 | | -2v+8=2 | | -.23(-.194)+.2(-.194-2)= | | -1/2x-7-11 | | x+6/3=-4 | | A+18=5a-3+a | | 11x+2/-8=-3 | | -4(2x-4)=-9*48 | | -95.66=3.5+7.4(-1.4n-3.6) | | m-8=26 | | x-5/3x+1 | | 13x+24/10-20=-15 | | 8xy+40x= | | (5-x)*(3-x)*(-6-x)+18=0 | | 18x(-5)=3(6x-2) |